Do Firms Manage Their Earnings During Initial Public Offerings? - Fuad Rakhman, Fuad Rakhman (The Indonesia Institute of Accountant Compartemen of Accounting Educators, 2013)
Abstract: This study investigates if IPO firms in Indonesia manage their earnings around the time of their IPo. Using financial data from 1999 to 2012, I examine the abnormal accruals of IPO firms during the three years prior to their IPO year and in their IPO year. I find that issuing firms managed their earnings starting two years prior to their IPO year and that earnings management was most profound in the IPO year. Further tests indicate that firms used income-increasing accruals during the period leading to the IPo. These findings are consistent with the view that firms manage their earnings to maximize the initial offer price and the proceeds from the IPo. Keywords: initial public offering, earnings management, accruals